Quantitative Proteomic Analysis Identifies MAPK15 as a Potential Regulator of Radioresistance in Nasopharyngeal Carcinoma Cells - Li, Zhanzhan; Li, Na; Shen, Liangfang; Fu, Jun (Frontiers in Oncology, 2018)
Resistance to radiotherapy remains a significant problem for the clinical management of nasopharyngeal cancer. Further understanding on the mechanisms of radioresistance would be necessary in order to develop more effective treatment for NPC and improve patient prognosis. Integrated quantitative proteomic approach involving TMT labeling and LC-MS/MS was used to identify proteins potentially responsible for radioresistance of NPC. KEGG analysis and protein-protein interaction enrichment analysis were conducted to identify enriched pathways in radioresistant NPC cells. Clonogenic survival assay, CCK-8 viability assay and BrdU incorporation analysis were used to examine the differential radiosensitivity in NPC model cells. Apoptosis of NPC cells after exposure to irradiation was detected using Caspase-3 Colorimetric Assay. Intracellular reactive oxygen species was detected by dichlorofluorescin diacetate fluorescent probe. In total, 5,946 protein groups were identified, among which 5,185 proteins were quantified. KEGG pathway analysis and protein-protein interaction analysis revealed robust activation of multiple biological processes/pathways in radioresistant CNE2-IR cells. MAPK15, one of up-regulated protein kinases in CNE2-IR cells, was selected for further investigation. Knockdown of MAPK15 expression significantly impaired clonogenic survival, decreased cell viability and increased cell apoptosis following exposure to irradiation in CNE2-IR cells; while over-expression of MAPK15 promoted cell survival, induced resistance to radiotherapy and reduced apoptosis in NPC cell lines CNE1, CNE2 and HONE1. Further, MAPK15 might regulate radioresistance through attenuating ROS accumulation and promoting DNA damage repair after exposure to irradiation in NPC cells. Quantitative proteomic analysis revealed enormous metabolic processes/signaling networks potentially involved in radioresistance in NPC cells. MAPK15 might be a potential regulator of radioresistance through attenuating ROS accumulation and enhancing DNA damage repair in NPC cells. Targeting MAPK15 might be useful in sensitizing cancer cells to radiotherapy in NPC.